Investigating the prevalence of three medically important pathogens in Ixodes pacificus from southern Oregon - Partin, Andrew T.; DeBess, Emilio E.; Spinks, Phillip Q.; Yabsley, Michael J.; Garrett, Kayla B.; Clover, James R.; Taylor, Geoffrey R. (Frontiers in Parasitology, 2025)
IntroductionIn the far western United States of America, Ixodes pacificus is the primary vector of several pathogens of public health and veterinary importance including the Lyme disease spirochete Borrelia burgdorferi sensu lato (s.l.), as well as Borrelia miyamotoi and Anaplasma phagocytophilum. Ixodes pacificus is common in southern Oregon yet there are few published studies on the distribution of tick-borne pathogens in this region. MethodsUsing real-time quantitative PCR, we assessed the prevalence of B. burgdorferi s.l., B. miyamotoi, and A. phagocytophilum among 2,463 unfed I. pacificus adults and nymphs combined into 260 pools (131 nymph, 129 adult) with nearly equal numbers of each life stage from 12 locations in Jackson County, Oregon. ResultsIn our study, 27.9% (36/129) and 29.8% (39/131) of adult and nymph pools, respectively, tested positive for at least a single pathogen. Nymph pools had a higher pool positivity rate (PPR) for B. burgdorferi s.l. with 15.3% (20/131) testing positive compared to 3.1% (4/129) of adult pools. Nymph pools also had a higher minimum infection rate (MIR) and maximum-likelihood estimate of pooled prevalence (EPP) for B. burgdorferi s.l. than adults. Interestingly, the prevalence of B. burgdorferi s.l. varied greatly in nymph pools across collection sites (0-70%). PPR of B. miyamotoi was 21.7% (28/129) for adults and 12.2% (16/131) for nymphs, making it the most frequently detected pathogen in adult pools and the most detected pathogen overall. Anaplasma phagocytophilum was the least frequently detected pathogen overall with a PPR of 3.1% (4/129) and 2.3% (3/131) for adults and nymphs, respectively. DiscussionThese findings underscore the importance of continued surveillance, pathogen testing, and public education regarding ticks in areas such as southern Oregon where I. pacificus is common but little research has been done.